IBM IN DESA TUA TUNU INDAH THROUGH MARKETING STRATEGY BASED ON INFORMATION TECHNOLOGY - Vebtasvili Vebtasvili; Desy Yuliana Dalimunthe (Journal of Innovation and Applied Technology, 2017)
This activity is conducted on Small and Medium Micro Enterprise (UMKM) "Raja Abon Makmur Lestari". In carrying out its business, MSME requires the right business planning and marketing strategy to prepare the business in the development of its business into a bigger and stronger business. This devotional activity provides the delivery of materials and direct practice of website creation and recording training - reporting of MSME financial statements. This activity is conducted by lecture, question and answer method and discussion. This method is used as a medium of communication during the training so that there is two-way communication between the speakers and the perpetrators of SMEs. Activities include the delivery of materials and direct practice of website creation and recording training - reporting of MSME financial statements. The results of the implementation of this activity are (1) Knowledge and understanding of MSME actors in making and using the website to be increased. (2) The existence of MSME website is expected to assist in information technology based marketing strategy in increasing sales. (3) The skills of MSMEs actors in recording and preparing financial statements are increasing, so it is possible to make their own financial report.